Peculiarities of Unsocial Behavior of Young People of Ukraine in the XXth Century: Historical Aspect - Zozulyak-Sluchyk Rоksolyana; Ketsyk, Ulyana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article deals with the problem of unsocial behavior of young people in Ukraine in the XXth century. At that time Ukraine was in the structure of former Soviet Union (1917-1991). In Soviet times the theory of unsocial phenomena could not freely develop because the unsocial phenomena were considered as an acquisition of capitalist society. For a long time researches about alcoholism, drug addiction, criminality, sexual demoralization, and others were closed and their results were not presented for a public discussion. Nevertheless certain traditions in research of the separate phenomena of un sociality were successfully formed in pre-soviet times. First of all it concerns the researches of suicides, criminality and alcoholism. The views of scientists on reasons of unsocial behavior in Ukraine in the ХХth century are analyzed by authors in this paper.